3.9k views
5 votes
Does someone mind helping me with this? Thank you!

Does someone mind helping me with this? Thank you!-example-1

2 Answers

7 votes


\displaystyle\\Answer:\ y=-(3)/(2)x+1

Explanation:

The condition of perpendicularity of the two lines given by the equations:


\displaystyle\\\left \{ {{y_1=m_1x+b_1} \atop {y_2=m_1x+b_2}} \right.

is the relation: m₁ x m₂=-1


\displaystyle\\Hence,\ m_2=-(1)/(m_1)


\displaystyle\\Given: y=(2)/(3)x+(2)/(3)\ == > \ m_1=(2)/(3) \\\\Thus,\ m_2=-(1)/((2)/(3) ) \\\\m_2=-(3)/(2)

The equation of the Point-Slope Form is expressed as:

y-y₁=m(x-x₁)

(-2,4) that is x₁=-2 y₁=4


\displaystyle\\Therefore,\\\ y-4=-(3)/(2) (x-(-2))\\\\y-4+4=-(3)/(2) (x+2)+4\\\\y=-(3)/(2)(x)-(3)/(2)(2) +4\\\\y=-(3)/(2)x -3+4\\\\y=-(3)/(2)x+1

User DOxxx
by
5.0k points
5 votes

Try the slop formula. x1 - x2 over y1 - y2. Also, try to cross multiply what you already have.

User Piotr Szmyd
by
4.8k points